2012
DOI: 10.1029/2011wr010588
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale assimilation of Advanced Microwave Scanning Radiometer–EOS snow water equivalent and Moderate Resolution Imaging Spectroradiometer snow cover fraction observations in northern Colorado

Abstract: [1] Eight years (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) of Advanced Microwave Scanning Radiometer-EOS (AMSR-E) snow water equivalent (SWE) retrievals and Moderate Resolution Imaging Spectroradiometer (MODIS) snow cover fraction (SCF) observations are assimilated separately or jointly into the Noah land surface model over a domain in Northern Colorado. A multiscale ensemble Kalman filter (EnKF) is used, supplemented with a rule-based update. The satellite data are either left unscaled or are scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
188
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(190 citation statements)
references
References 86 publications
(117 reference statements)
1
188
0
1
Order By: Relevance
“…However, GRACE TWS retrievals feature a very coarse resolution (around 100 km) so that they would only be useful in conjunction with fSCA retrievals for very large scale applications. On the other hand, the use of higher-resolution PM SWE retrievals (order 25 km) in the assimilation has shown particular promise (e.g., De Lannoy et al, 2012;Li et al, 2017). At the same time, PM SWE retrievals are not accurate in complex topography and forested areas, nor for wet and deep snowpacks (Foster et al, 2005), which might limit the applicability of such multisensor assimilation approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, GRACE TWS retrievals feature a very coarse resolution (around 100 km) so that they would only be useful in conjunction with fSCA retrievals for very large scale applications. On the other hand, the use of higher-resolution PM SWE retrievals (order 25 km) in the assimilation has shown particular promise (e.g., De Lannoy et al, 2012;Li et al, 2017). At the same time, PM SWE retrievals are not accurate in complex topography and forested areas, nor for wet and deep snowpacks (Foster et al, 2005), which might limit the applicability of such multisensor assimilation approaches.…”
Section: Discussionmentioning
confidence: 99%
“…De Lannoy et al (2010 used the EnKF in a twin experiment to assimilate synthetic PM SWE retrievals and greatly outperformed the OL. This was extended to a real multisensor experiment by jointly assimilating PM SWE and MODIS fSCA retrievals (De Lannoy et al, 2012). Li et al (2017) used the ES to assimilate PM SWE retrievals and estimate the SWE distribution, markedly outperforming the OL.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have already shown the added value of DA in snow-dominated watersheds to improve the estimation of the state of the watershed (De Lannoy et al, 2012;Dechant and Moradkhani, 2011;Nagler et al, 2008;Slater and Clark, 2006;Andreadis and Lettenmaier, 2006). Some studies have also integrated DA in ensemble forecast systems for relatively short-term (up to 5-10 days) hydrologic forecasts (Abaza et al, 2014(Abaza et al, , 2015He et al, 2012), but studies focusing on longer forecast periods are scarce even though the need exists for water resource managers.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the KF and EKF schemes, this method does not require a model linearization since the error estimates are evaluated from an ensemble of possible model realizations using the Monte Carlo approach (Evensen, 2003). In the recent past, an increasing number of 15 studies on snow hydrology have contributed to confirm the EnKF as a well-performing technique enabling to enhance the accuracy of hydrological simulations by consistently updating model predictions through the assimilation of snow-related observations (Andreadis and Lettenmaier, 2005;Durand and Margulis, 2006;Clark et al, 2006;Slater and Clark, 2006;Su et al, 2008;Durand and Margulis, 2008;Su et al, 2010;De Lannoy et al, 2012;Magnusson et al, 2014;Griessinger et al, handling systems nonlinearities, PF schemes are currently garnering a growing attention for snow modelling applications. Leisenring and Moradkhani (2011) compared the performances of common sequential EnKF-based DA methods and PF variants at assimilating synthetic SWE measurements to improve its seasonal predictions and to estimate some sensitive parameters in a small-scale snowpack model.…”
Section: Introductionmentioning
confidence: 99%